The Ventilator Management Team: Repurposing Anesthesia Workstations and Personnel to Combat COVID-19. (September 2020) - Canelli, Robert; Spence, Nicole; Kumar, Nisha; Rodriguez, Gerardo; Gonzalez, Mauricio
The coronavirus disease 2019 pandemic resulted in unprecedented numbers of patients with respiratory failure requiring ventilatory support. The number of patients who required critical care quickly outpaced the availability of intensive care unit (ICU) beds. Consequently, health care systems had to creatively expand critical care services into alternative hospital locations with repurposed staff and equipment. Deploying anesthesia workstations to the ICU to serve as mechanical ventilators requires equipment preparation, multidisciplinary planning, and targeted education. We aim to contextualize this process, highlighting major differences between anesthesia workstations and ICU ventilators, and to share the insights gained from our experiences creating an anesthesia provider-based ventilator management team.